Analisis Kinerja Divisi Penghimpunan di Lazisnu Kabupaten Mojokerto - Ulin Nuha, Mohamad; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2025)
Nahdlatul Ulama' as the largest Islamic organization in Indonesia has a large mass base. The potential of zakat, infaq and shodaqoh (ZIS) funds is also estimated to be directly proportional to the amount of time. Lazisnu as an institution that is part of nahdlatul ulama' has the responsibility to manage these funds, including to collect them. Therefore, the fundrising division is the main focus in this study. One of the lazisnu service offices is Lazisnu Mojokerto Regency. This study aims to determine the performance and evaluation of the fundrising division in Lazisnu Mojokerto Regency by using a qualitative approach through data collection through observation, interviews and documentation. The results of this study show that Lazisnu Mojokerto Regency in the performance of its fundrising division prioritizes direct fundrising through formation UPZIS and JPZIS, but also continues to carry out indirect fundrising, although not optimally. The performance of the fundrising division still needs to be improved through evaluation and also by setting targets. The tradition of distributing zakat, especially zakat fitra, must also be a spesial focus through understanding and socialization.